Autoesquemas y habilidades sociales en adolescentes con diagnóstico de labio y paladar hendido - Vinaccia , Stefano (2022)
The purpose of this research was to evaluate the relationship of the self-schemes and social skills of 49 adolescents of both genres with a diagnosis of cleft lip and palate in the city of Medellin, Colombia. The design of the study was exploratory- descriptive-transversal-correlational. The Schemes Questionnaire (CIE) and the Scale of Social Skills EHS were used as instruments. The outcomes did not demonstrate clinically significant levels in the variables of the study; the scores of the self-schemes and the social skills reported by the adolescents with cleft lip and palate were generally good. Finally, the whole study had a Cronbach Alfa above .